(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2018)
Social Media Platforms are the platforms that give individuals the opportunity to interact, using two way communication. It means that anyone who has got an online account can share their opinions with other social media users. Every other person is now using the Social Media; no matter what their age or gender is. So, it becomes extremely important to understand how it influence the scholastic development and performance of the students. The young generation is the one that is caught in the rapid technological advancements and developments. This study is focussed to find out whether Social Media like Facebook affects the performance of students academically. The findings shows that there is no relationship between social media and scholastic performance as it is clearly projected in their overall grade average which doesn’t change with the number of hours spent on social media. Neither does it affect the amount of time they invest in studying.